Fichte y la ilustración: de la defensa de la libertad de expresión a la exhortación al pensamiento autónomo - Sole, Maria Jimena (2020)
The aim of this article is to examine Fichte’s attitude toward what can be considered the kernel of the Kantian Enlightenment program, that is, the ideal of emancipation through the autonomous exercise of one’s own reason. To this end, I analyze two works written and published a little more than a decade apart: the Zurückforderung der Denkfreiheit (1793), in which Fichte fervently defends the Enlightenment as the goal towards which humanity progresses, and Die Grundzüge des gegenwärtigen Zeitalters (1804 and 1805), where he expresses a harsh criticism of his own time, the Enlightenment era. I will show that despite the evident change in his attitude towards the Enlightenment, Fichte not only adheres to the Kantian Enlightenment program but also radicalizes it. This can be seen, according to my interpretation, in the claim for unlimited freedom of expression and in the priority he awards to oral communication over written communication. To conclude, I raise the possibility that Fichte defends a positive Enlightenment that, unlike the negative and empty one he rejects, remains faithful to the end of emancipation and autonomous thought, and achieves it by effective means.